A Study of the Original Drawings of the Hejaz Railway Headquarters Building - Irgin Uzun, Turkan; El Abidin, Mahmoud Zein (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
The Hejaz Railway, considered the last major project of the Caliphate, was an important project of the Ottoman Empire in the second half of the 19th century. Books, articles and theses were written about the project by numerous domestic and foreign researchers, but the Hicaz Railway Muduriyyet-i Umumiyesi Project, which was meant to serve and strengthen the region, was never truly completed. This study is a review of the original drawings found in the archives of the General Directorate of Foundations and some 6000 BOA documents, as well as the historical and political developments related to the project. The plan and facade features of this high-quality project supported by the empire and reflecting the style of the national architect have been introduced for the first time in detail with evaluations of the architectural approach. The aim of this article was to provide new insight and information to researchers on the work of architects Kemaleddin, Ali Talat and Mukbil Kemal.
Keywords: Abdul Hamid II period architecture; Ali Talat Bey; Hejaz Railway headquarters building; the Hejaz Railway Mudiriyyet-i Umumiyye Building Project; national architecture; architect Kemaleddin Bey; architectural history; Mukbil Kemal; Ottoman architecture; Architecture